Resveratrol and Neuroprotection: Impact and Its Therapeutic Potential in Alzheimer's Disease - Md. Habibur Rahman; Rokeya Akter; Tanima Bhattacharya; Mohamed M. Abdel-Daim; Mohamed M. Abdel-Daim; Saad Alkahtani; Mohammed W. Arafah; Norah S. Al-Johani; Norah M. Alhoshani; Nora Alkeraishan; Alhanof Alhenaky; Omar H. Abd‐Elkader; et al. (Frontiers Media S.A., 2020)
Alzheimer's disease (AD) is a progressive cortex and hippocampal neurodegenerative disease which ultimately causes cognitively impaired decline in patients. The AD pathogen is a very complex process, including aggregation of Aβ (β-amyloid peptides), phosphorylation of tau-proteins, and chronic inflammation. Exactly, resveratrol, a polyphenol present in red wine, and many plants are indicated to show the neuroprotective effect on mechanisms mostly above. Resveratrol plays an important role in promotion of non-amyloidogenic cleavage of the amyloid precursor protein. It also enhances the clearance of amyloid beta-peptides and reduces the damage of neurons. Most experimental research on AD and resveratrol has been performed in many species, both in vitro and in vivo, during the last few years. Nevertheless, resveratrol's effects are restricted by its bioavailability in the reservoir. Therefore, scientists have tried to improve its efficiency by using different methods. This review focuses on recent work done on the cell and animal cultures and also focuses on the neuroprotective molecular mechanisms of resveratrol. It also discusses about the therapeutic potential onto the treatment of AD.